EFFECTIVENESS OF STRATEGIES BASED ON MIND MAPPING ON ACHIEVEMENT IN PROBLEM SOLVING ABILITY OF P.U. COLLEGE STUDENTS - Mahadev, Ambika; Narayanappa, Venkoba (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study highlights the value of effectiveness of strategies based on mind mapping on achievement in problem solving ability. Problem-solving skills are the ability to identify problems, brainstorm and analyze answers, and implement the best solutions. The students with good problem-solving skills is a self-achiever and they are proactive in understanding the root of a problem and work with actively to consider a wide range of solutions before deciding how to move forward. The main purpose of the study is to improve teaching effectiveness, learners’ participation. The aim of this study is to identify effectiveness of the mind mapping strategy on achievement in problem solving ability of P.U. college students. To investigate the significant difference in the ‘pre’ and ‘post’ mean Attention scores of students taught through mind mapping strategy.